Parenting Patterns in Improving Adolescents' Religious Understanding - Dinul Yusra; Imam Tabroni (PT FORMOSA CENDEKIA GLOBAL, 2022)
Adolescence is a period of transition or change from children to adults. There will be many things they can learn from the people around them. If teenagers get good parenting or social relationships, they will survive various mental stresses. As adolescence goes on, the role of parents is very important to equip children's growth and development to be in accordance with what is expected. Because parents are the first education for their children in the family environment. The family can also sometimes be called the first education for children in their environment, because from everything that parents or families do, their children will see and practice it. Therefore, the role of parents and families is very important for increasing children's religious understanding in adolescence. In this regard, the purpose of this study is to determine parenting patterns in the religious understanding of adolescents. The research method used is descriptive qualitative research and participatory action research. This research is a community study for families who are Muslim and have teenage children aged 10 to 20 years. Data collection was carried out by holding religious activities at the mosque through the Ar-Rahmah Mosque Youth Association (IRMAR).